A meta-analysis to determine the effect of coagulopathy on intracranial haematoma progression in adult patients with isolated blunt head trauma. (October 2015) - Batchelor, John S
Coagulopathy following isolated traumatic brain injury is a well-recognised complication especially in patients with severe head injury. Intracranial haematoma progression is a major adverse factor affecting outcome in patients with traumatic brain injury. Coagulopathy is an important risk factor for haematoma progression. The aim of this meta-analysis was to determine the magnitude of effect of coagulopathy on intracranial haematoma progression in patients with isolated traumatic brain injury. Studies comparing patients with traumatic brain injury, coagulopathy and haematoma progression to patients with traumatic brain injury, haematoma progression and no coagulopathy were identified. The search was performed using Medline via the PubMed interface; no limits were placed on the language. In total 12 studies were identified as being suitable for the meta-analysis. Significant heterogeneity was present between the studies as demonstrated by an I 2 = 80.185. The fixed effects model was considered to be the preferred model and this produced a pooled odds ratio of 6.897 (95% confidence interval: 5.495–8.655). The results of this meta-analysis show that traumatic brain injury-induced coagulopathy is a significant factor in haematoma progression in patients with isolated traumatic brain injury.